Towards Responsible Mining: The Imperative Integration of Geoethics into Cuban Mining Engineering - Cervantes-Guerra, Yosbanis Manuel; Carbonell-Pupo, Arlenys; Cervantes-Barzaga, Kevin (Minería y Geología, 2025)
Mining activity in Cuba, a fundamental pillar of its economy, faces the critical challenge of harmonizing resource extraction with environmental protection and social development. This article argues for the imperative need to systematically integrate geoethics into the education of Cuban mining engineers, positing that traditional, robust technical training is insufficient to address contemporary complex socio-environmental dilemmas. Through conceptual analysis and a critical review of the mining engineering curriculum, existing educational gaps are identified. A dual curricular model is proposed, one that mainstreams geoethical principles across technical subjects and establishes a specific, mandatory core course. The study concludes that this integration is essential for cultivating responsible professional praxis, ensuring the social license to operate, and transitioning towards a sustainable and ethically responsible mining model in Cuba, one that guarantees both profitability and ecological integrity, as well as community well-being.